The Diverse AAA+ Machines that Repair Inhibited Rubisco Active Sites - Mueller-Cajar, Oliver (Frontiers in Molecular Biosciences, 2017)
Gaseous carbon dioxide enters the biosphere almost exclusively via the active site of the enzyme ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco). This highly conserved catalyst has an almost universal propensity to non-productively interact with its substrate ribulose 1,5-bisphosphate, leading to the formation of dead-end inhibited complexes. In diverse autotrophic organisms this tendency has been counteracted by the recruitment of dedicated AAA+ (ATPases associated with various cellular activities) proteins that all use the energy of ATP hydrolysis to remodel inhibited Rubisco active sites leading to release of the inhibitor. Three evolutionarily distinct classes of these Rubisco activases (Rcas) have been discovered so far. Green and red-type Rca are mostly found in photosynthetic eukaryotes of the green and red plastid lineage respectively, whereas CbbQO is associated with chemoautotrophic bacteria. Ongoing mechanistic studies are elucidating how the various motors are utilizing both similar and contrasting strategies to ultimately perform their common function of cracking the inhibited Rubisco active site. The best studied mechanism utilized by red-type Rca appears to involve transient threading of the Rubisco large subunit C-terminal peptide, reminiscent of the action performed by Clp proteases. As well as providing a fascinating example of convergent molecular evolution, Rca proteins can be considered promising crop-improvement targets. Approaches aiming to replace Rubisco in plants with improved enzymes will need to ensure the presence of a compatible Rca protein. The thermolability of the Rca protein found in crop plants provides an opportunity to fortify photosynthesis against high temperature stress. Photosynthesis also appears to be limited by Rca when light conditions are fluctuating. Synthetic biology strategies aiming to enhance the autotrophic CO2 fixation machinery will need to take into consideration the requirement for Rubisco activases as well as their properties.